Evaluating cardiovascular risk in chronic kidney disease patients: a biomarker approach - Abdul Halim Abdul Gafor,; Rozita Mohd,; Rizna Cader,; Kong, Wei Yen; Marlyn Mohamad,; Shamsul Azhar Shah,; Arbaiyah Bain,; Norella CT Kong, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Cardiovascular disease (CVD) is a major cause of morbidity and mortality in chronic kidney disease (CKD) patients. This study aimed to determine the roles of CVD biomarkers in CKD patients. This was a case-control study which recruited consecutive patients with stage 2-4 CKD patients with and without CVD. Serum levels of highly-sensitive C reactive protein (hs-CRP), cystatin C (CysC), asymmetrical dimetylarginine (ADMA) and symmetrical dimethylarginine (SDMA) were measured. Sixty two stage 2-4 CKD patients with a mean age of 60.3 ± 10.4 years were recruited. Twenty three (37.1%) of them had CVD. Those CKD patients with CVD were older (64.1±8.0 vs 58.1± 1.1, p<0.05) and had significantly higher systolic blood pressure (139.4 ± 16.2 vs 129.4 ± 14.8 mmHg, p<0.05). Diabetic patients had 8 times (95% CI 1.25-51.77, p< 0.05) higher risk to develop CVD. CKD patients with CVD had a higher serum creatinine (185.0 ± 54.1 vs 154.1 ± 54.4 μmol/L, p<0.05), a lower estimated glomerular filtration rate (33.7 ± 12.2 vs 42.2 ± 14.5 mL/min/1.73m2 p<0.05) and a lower triglyceride levels (1.3 (1.1-1.7) vs 1.8 (1.4-2.3) mmol/L, p<0.05), compared to those without CVD. Fasting blood sugar was 7.1 ± 2.7 mmol/L in CVD group and 6.3 ± 1.6 mmol/L in non CVD group (p>0.05). There were no differences in their mean serum levels of hs-CRP, CysC, ADMA and SDMA. Risk factors including age, diabetes mellitus, hypertension and renal functions were still the most important CVD risk factors in CKD patients.